A Window into the Soul of International Arbitration: Arbitrator Selection, Transparency and Stakeholder Interests - Rogers, Catherine (Victoria University of Wellington Law Review, 2015)
New Zealand Law Foundation International Dispute Resolution Lecture 2013, delivered at Stone Lecture Theatre, University of Auckland Faculty of Law, 26 November 2013. This essay derives from that lecture, which considers the important issue of arbitrator selection, appointment and challenge standards and procedures, and introduces the Arbitrator Intelligence project – a proposed solution for informational asymmetries that can affect the fairness of arbitrator selection and appointment.